2008
DOI: 10.1002/prca.200780076
|View full text |Cite
|
Sign up to set email alerts
|

Myofilament proteins: From cardiac disorders to proteomic changes

Abstract: Myofilament proteins of the cardiac sarcomere house the molecular machinery responsible for generating tension and pressure. Release of intracellular Ca 21 triggers myofilament tension generation and shortening, but the response to Ca 21 is modulated by changes in key regulatory proteins. We review how these proteomic changes are essential to adaptive physiological regulation of cardiac output and become maladaptive in cardiac disorders. We also review the essentials of proteomic techniques used to study myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 124 publications
(167 reference statements)
0
24
0
Order By: Relevance
“…Myofilament protein PTMs have emerged as a key mechanism regulating cardiac contractility, and increasing evidence has shown that the alteration of myofilament protein PTMs, particularly phosphorylation, can contribute to contractile dysfunction and heart failure [912, 25, 26, 29, 30]. Additionally, studies in humans, as well as large and small animals, have shown that aging and pathological cardiac conditions induce transmural changes in contractile function that correlate with differences in the modification status of myofilament proteins [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myofilament protein PTMs have emerged as a key mechanism regulating cardiac contractility, and increasing evidence has shown that the alteration of myofilament protein PTMs, particularly phosphorylation, can contribute to contractile dysfunction and heart failure [912, 25, 26, 29, 30]. Additionally, studies in humans, as well as large and small animals, have shown that aging and pathological cardiac conditions induce transmural changes in contractile function that correlate with differences in the modification status of myofilament proteins [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Contractile heterogeneity, in particular, has taken on increased significance with the demonstration that transmural changes in myocardial contractility not only occur in the failing heart [13], but may also be predictive of adverse cardiac events [7, 8]. Myocardial contractility is governed by a number of factors, including the size and duration of Ca 2+ transients, as well as the intrinsic properties of the contractile apparatus, which depend primarily on the expression of myofilament protein isoforms and post-translational modifications (PTMs) [912]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Aberrant protein PTMs together with mutations and alternatively spliced isoforms are increasingly recognized as important underlying mechanisms for cardiovascular diseases. 1214 Hence, a comprehensive analysis of protein modifications is of high importance for understanding the disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, most studies of post-translational modifications (PTMs) of cardiac myofilaments addressed more common PTM types such as phosphorylation, glycosylation and proteolysis. 14-17 …”
mentioning
confidence: 99%